Sjöfartens tillväxt, utifrån ett Arktiskt perspektiv - möjlighet eller begränsning - Grösfjeld, Emelie; Lund Askoldova, Liza (Chalmers tekniska högskola / Institutionen för sjöfart och marin teknik, 2016)
The melting of the polar ice opens up new opportunities for the shipping industry. Enough ice has melted in the Northern Sea route through the Arctic. This gives the opportunity for several segments of the shipping industry so they could use it. This study examines the opportunities that now exists and how they will develop in the future. This in order to provide the liner shipping, particularly container shipping, with information regarding the use of the Northeast Passage in the Arctic. Great emphasis has been placed on the possibility of the growth of shipping in the Arctic and criteria to achieve profitability of shipping in the Arctic. To get the most accurate overall picture as possible, for the possibility of using the maritime transport in the Arctic, different approaches has been used. Among those qualitative methods. Comparison of two different routes between two destinations has been analysed. One route intends to use the Suez Canal and the other route goes through the Northeast Passage. Method combinations where comparisons and interviews has provided a broad overview and an increased accuracy in the result. The result shows that the Northeast Passage in the future very well may be a possible alternative to the Suez Canal.